To harness discontent: Michelle Obama’s becoming as African American autobiography - Kovács, Ágnes Zsófia (AMERICANA E-journal of American Studies in Hungary, 2018)
Michelle Obama’s Becoming has become the best known memoir by an ex-First Lady ever. Traditional as the First Lady’s role and the First Lady’s memoir genre are, Becoming has shifted the terms through which to define both. Instead of the insider’s story about the public husband by the domestic wife it represents the basic American story of a self-made strong woman invested in the life of the community. This paper reads Becoming and charts its statements about finding one’s voice, opting to work for the community, and choosing hope over despair as not so much a personal but rather as a communal story of a not so well definable group. To get a better glimpse of the actual appeal of the story, the paper investigates where this project comes from, what its modes of existence are, how it is circulated, what subject positions it determines. Becoming can be read as political commentary in the sense of antebellum autobiographical slave narratives that had aimed to trigger political change by personal testimony. Another intertextual influence can be African American women’s fiction and autobiography where the theme of finding one’s voice in the context of double oppression is vital. The story defines the subject position of an ‘empowered’ black feminine subject.